HIITing the brain with exercise: mechanisms, consequences and practical recommendations. (1st June 2020) - Calverley, Thomas A.; Ogoh, Shigehiko; Marley, Christopher J.; Steggall, Martin; Marchi, Nicola; Brassard, Patrice; Lucas, Samuel J.E.; Cotter, James D.; Roig, Marc; Ainslie, Philip N.; Wisløff, Ulrik; Bailey, Damian M.
Abstract: The increasing number of older adults has seen a corresponding growth in those affected by neurovascular diseases, including stroke and dementia. Since cures are currently unavailable, major efforts in improving brain health need to focus on prevention, with emphasis on modifiable risk factors such as promoting physical activity. Moderate‐intensity continuous training (MICT) paradigms have been shown to confer vascular benefits translating into improved musculoskeletal, cardiopulmonary and cerebrovascular function. However, the time commitment associated with MICT is a potential barrier to participation, and high‐intensity interval training (HIIT) has since emerged as a more time‐efficient mode of exercise that can promote similar if not indeed superior improvements in cardiorespiratory fitness for a given training volume and further promote vascular adaptation. However, randomised controlled trials (RCTs) investigating the impact of HIIT on the brain are surprisingly limited. The present review outlines how the HIIT paradigm has evolved from a historical perspective and describes the established physiological changes including its mechanistic bases. Given the dearth of RCTs, the vascular benefits of MICT are discussed with a focus on the translational neuroprotective benefits including their mechanistic bases that could be further potentiated through HIIT. Safety implications are highlighted and components of an optimal HIIT intervention are discussed including practical recommendations. Finally, statistical effect sizes have been calculated to allow prospective research to be appropriately powered and optimise the potential for detecting treatment effects. Future RCTs that focus on the potential clinical benefits of HIIT are encouraged given the prevalence of cognitive decline in an ever‐ageing population. Abstract : Abstract figure legend: Summary of the integrated mechanisms and functional adaptations underpinning high‐intensity interval training‐induced neuroprotection High‐intensity interval training (HIIT) represents a more time‐efficient mode of exercise that can potentiate cardiorespiratory fitness and further enhance neuroprotection compared to more traditional moderate‐intensity continuous training paradigms. While the precise mechanisms remain unclear, prolonged exposure to the mechanical forces associated with the intermittency of HIIT‐induced sinusoidal hyperaemia can promote complex changes in the cerebral pressure, strain and shear stress phenotype to induce functional–structural adaptation of the vascular wall subsequent to endothelial cell mechanotransduction. Redox activation of complex intracellular signalling cascades can translate into molecular, haemodynamic and structural adaptations that ultimately enhance neuroprotection. Establishing these mechanisms more clearly will provide an evidence base for the prescription and future optimisation of HIIT interventions that have arguably more potential to promote healthy ageing by delaying stroke, cognitive decline and dementia. Digits below each of the integrated functionally adaptive benefits proposed (bottom of figure) highlight sample size estimates (number of participants/patients required to achieve adequate statistical power) to inform the design of future randomised control trials.